Polish Writers and their Influence on Women’s Public Activity: A Case Study of Józefa Kisielnicka and Eliza Orzeszkowa - Dajnowicz, Małgorzata (Respectus Philologicus, 2015)
Józefa Kisielnicka (1865–1941) created a new model of a woman in the society, a woman that is actively involved in the public life and concentrates on the charity work and educational needs of the people in their close environment. Her attitude towards women’s involvement in the public life was greatly appreciated by both men and women, especially among the gentry class. In her literary works (published, e.g., in Warsaw Courier and Daily Courier), she depicted women’s everyday life. The general image of her characters was very negative. Eliza Orzeszkowa (1841–1910) can be described as a great activist in initiating and developing the idea of gender issues, both in her written works and everyday life duties. Her political views, social involvement, and literary achievements were widely recognized among women representing liberal political views. Her numerous works (for example, A Few Words about Women) related to the place of the women in the society and the issues of gender equality. Eliza Orzeszkowa considered the cultural and social conditions, which influenced the possibilities of women in their pursuit of equality. The two women writers Józefa Kisielnicka and Eliza Orzeszkowa set a new pattern of initiating and shaping the public involvement of women in the northeastern province of Poland.